TRANSFORMASI PENGELOLAAN KEUANGAN DIGITAL PADA SANTRI PONDOK PESANTREN AL FALAH PUTERI BANJARBARU - Mukhlis Kaspul Anwar (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
Digital transformation in financial management at Al-Falah Islamic Boarding School in Banjarbaru is becoming important along with the increasing use of technology. This study aims to analyze the process of transitioning from cash to electronic money, and its impact on the financial management of Islamic boarding schools. The method used is qualitative with a descriptive approach, involving in-depth interviews and participatory observation of students and Islamic boarding school managers. The results of the study indicate that the use of electronic money increases efficiency and security in financial transactions. However, there are challenges faced, such as low financial literacy among students which hinders the optimal use of electronic money. Education and socialization regarding the use of e-wallets are needed to help students understand the benefits and risks in digital financial management. These findings indicate that financial transformation not only prioritizes technical aspects, but also the importance of increasing financial knowledge and awareness in the Islamic boarding school environment as a step towards more modern and responsible financial management.